Analysis of Lexical Cohesion by Speech Indonesian Students in the United States - Ndruru, Murniwati; Johan, Mhd. (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
Finding cohesion and the kinds of lexical cohesion used by Indonesian students in the United States speech on YouTube social media is the goal of this study. The enunciation expressed by student speech produces sentences that contain lexical types by connecting sentence by sentence into one discourse, thus becoming a source of data in this research. After that the data found is analyzed by identification based on the kinds of lexical cohesion obtained from the data source using the theory by Halliday & Hasan, (1976) and also Platridge Brian, (2012) theory. This research discovered using descriptive qualitative methods. To collect the data was carried out using the observation technique. The study findings include a few expressions that combine to create sentences with the various lexical cohesion patterns observed in speech Indonesian students in the United States: 8 data repetition, 1 data synonymy, 4 data meronym, and 2 data collocation. Lexical cohesion is widely used by Indonesian students in the United States in speeches. Lexical cohesion functions to create coherence between the meanings of sentences by selecting vocabulary or lexemes. Lexical cohesion also functions to connect elements in discourse semantically.